A decision aid GIS-based risk assessment and vulnerability analysis approach for transportation and pipeline networks. (April 2016) - Inanloo, Bahareh; Tansel, Berrin; Shams, Kollol; Jin, Xia; Gan, Albert
Graphical abstract: Highlights: A framework for integrated assessment of service vulnerabilities was developed. A quantitative risk analysis was performed interactively on infrastructure networks. Vulnerable points along with the affected population were identified within the study area. Abstract: The objective of this study was to develop a framework for integrated assessment of service vulnerabilities based on individual system failure probabilities, consequences, and potential interactions with other infrastructure networks. A comprehensive integrated network methodology was developed to evaluate and quantify the interactions between different infrastructure networks which included transportation and pipeline systems for water and sewer services. The quantitative risks were performed in terms of the individual network vulnerabilities, interactions of different networks (traffic, water, sewer), affected service areas, number of vehicles, and delays in transportation (vehicle hours) using ArcGIS. The interactive vulnerability and quantitative risk assessment methodology was demonstrated by applying for the transportation and pipeline systems infrastructure for the service area in downtown Miami, Florida. The impacts on traffic flow were evaluated by segmentation based on the node-based connections and visualized using ArcGIS. Based on the analyses, about 3.15 square miles in the case study area (17.76 square miles) is vulnerable for service interruptions which will affect traffic flow significantly. This corresponds to about 58, 805 people in the service area. The integrated methodology developed can be used for asset management for developing effective maintenance programs to improve service quality in areas served by multiple infrastructure networks.